2016
DOI: 10.1051/rees/2016024
|View full text |Cite
|
Sign up to set email alerts
|

Influences of some parameters on the performance of a small vertical axis wind turbine

Abstract: Abstract. The effects of various parameters on the performance of a straight bladed vertical axis wind turbine, using the vortex model, have been numerically investigated. A vortex model has been used to evaluate the performance of a vertical axis wind turbine, by means of aerodynamic characteristics of different airfoils for Reynolds numbers between 10 5 and 10 6 . Parameters such as the thickness and the camber of the blade airfoil, the solidity, the type of blade profile, the number of blades and the pitch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…As noticed, for all cases, an increase in TSR leads to an increase in the obtained C p , which is expected. This trend matches well with existing literature, which shows that using the Vortex model, the C p for 3 bladed VAWTs is expected to rise until the TSR reaches the value of 5 [23]. The increase in C p was most experienced by VAWTs with a 0-degree blade pitch or with a negative 2-degree blade pitch and least with the 6-degree blade pitch.…”
Section: Resultssupporting
confidence: 89%
“…As noticed, for all cases, an increase in TSR leads to an increase in the obtained C p , which is expected. This trend matches well with existing literature, which shows that using the Vortex model, the C p for 3 bladed VAWTs is expected to rise until the TSR reaches the value of 5 [23]. The increase in C p was most experienced by VAWTs with a 0-degree blade pitch or with a negative 2-degree blade pitch and least with the 6-degree blade pitch.…”
Section: Resultssupporting
confidence: 89%
“…It was reported that the VAT has the lowest self-starting capability with NACA 0012 [8] and a highest capability with NACA 0021, among the various symmetric airfoils investigated [9]. Different blade geometries have been proposed and tested to improve the self-starting capability of the VAT [10][11][12][13][14][15][16]. The blade pitch control was also found to be an effective method for the VAT to have a better self-starting capability [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Vertical Axis Wind Turbines (VAWTs) have drawn much attention of research and industry due to their potential to be installed in urban and offshore regions, and in particular where the wind resource λ Tip speed ratio, ωR/V ∞ ω Rotational speed, rad/s presents highly variable wind speed and direction [1]. In order to understand its aerodynamics, many authors have used URANS Computational Fluid Dynamics (CFD) simulations to explore qualitatively the influence of the aerofoil profile [2,3,4,5], the pitch angle [6,7,8], Reynolds number [9,10,11,12] and the number of blades [1,13,7,14] on the power coefficient.…”
Section: Introductionmentioning
confidence: 99%